Applying the photovoice method with adolescents in mining areas in rural Mozambique: critical reflections and lessons learned - Olga Cambaco; Hermínio Cossa; Andrea Farnham; Eusébio Macete; Mirko S. Winkler; Karin Gross; Khátia Munguambe (Global Health Action)
There is a recognised need for innovative methods to elicit the perspective of adolescents on public health issues, particularly when addressing sensitive topics such as the impact of mining projects on their health. Participatory approaches such as “photovoice” allow for deep engagement of vulnerable and marginalised populations, including adolescents. However, few existing studies have used the photovoice method to reflect on issues related to the environment and its impact on public health. To date, no studies have been found that have used photovoice to gain insight into adolescentsʼ perspectives in mining areas. In this paper, we discuss the application of the photovoice method to understand adolescents’ perceptions about the impact of mining on their health and well-being in rural areas in Mozambique. The study was conducted in northern and central Mozambique. Photovoice was successfully integrated into eight focus group discussions with adolescent girls and boys aged 15 to 17 years. Several lessons for guiding future research were learned. First, it provided an understanding of the perceived impacts of mining on their health and well-being. Second, photovoice promoted active engagement and interest in the study by the adolescents. Finally, compared to its ability to capture perceptions of physical and environmental aspects affecting adolescents’ well-being, the method was less straightforward in revealing their concerns regarding social, relational and community aspects that are less tangible. Programs can make use of photovoice to address health issues without setting adolescents’ views and priorities aside, allowing them to influence health decisions on issues that are meaningful to them. Future studies should explore strategies to minimise the role of the power dynamics that affect the engagement and contribution of adolescents in advocating for necessary and meaningful changes. Additionally, it is important to investigate how health programs and policies can help to reduce the impact of existing inequalities.